2022
DOI: 10.1186/s12886-022-02626-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of visual outcomes of a diffractive trifocal intraocular lens and a refractive bifocal intraocular lens in eyes with axial myopia: a prospective cohort study

Abstract: Background To assess and compare the efficacy, safety, accuracy, predictability and visual quality of a diffractive trifocal intraocular lens (IOL) and a refractive rotationally asymmetric bifocal IOL in eyes with axial myopia. Methods This prospective cohort study enrolled patients with implantation of the diffractive trifocal IOL or the refractive bifocal IOL. Eyes were divided into four groups according to the IOL implanted and axial length. Man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Besides, we found that reflected from the similar CDVA among groups, EDOF IOLs offered reliable efficacy for the eye with various postoperative residual myopic refraction, even for the eyes targeted between − 2.25 to -1.50. Sun [ 19 ] and Steinwender [ 14 ] emphasized the superior corrected distance visual acuity achieved with the diffractive trifocal IOL. Sun et al [ 20 ] reported that trifocal IOL offered stable and satisfactory visual outcomes for eyes with long AL.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, we found that reflected from the similar CDVA among groups, EDOF IOLs offered reliable efficacy for the eye with various postoperative residual myopic refraction, even for the eyes targeted between − 2.25 to -1.50. Sun [ 19 ] and Steinwender [ 14 ] emphasized the superior corrected distance visual acuity achieved with the diffractive trifocal IOL. Sun et al [ 20 ] reported that trifocal IOL offered stable and satisfactory visual outcomes for eyes with long AL.…”
Section: Discussionmentioning
confidence: 99%
“…Previous clinical studies on MIOLs have used this device to report PP. For instance, Tañá-Sanz et al [ 14 ] reported a mean pupil size of 2.4 mm in a sample of patients with a mean age of 72 years, and Sun et al [ 15 ] reported a mean pupil size of 3.3 mm in a sample of patients with a mean age of 66 years. Other authors have also used Pentacam for reporting PP in their studies with mean pupil sizes in the range of 2.4 to 3.3 mm depending on the mean age of the sample [ 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%